Identification and quantitative analysis of phenolic glycosides with antioxidant activity in methanolic extract of Dendrobium catenatum flowers and selection of quality control herb-markers. (September 2019) - Zhang, Xinfeng; Zhang, Sijie; Gao, Beibei; Qian, Zheng; Liu, Jingjing; Wu, Shihua; Si, Jinping
Abstract: Recently, the flowers of Dendrobium catenatum ( D. officinale ) have been approved as new food ingredient. This study aimed to investigate the herb-markers and their antioxidant activities in methanolic extracts of D. catenatum flowers, and to establish the quality evaluation methods for raw materials and their products of flower by HPLC. The methanolic extract of 11 strains of D. catenatum flowers were found to contain a high content of total phenol and flavonoids, and they possessed potential antioxidant capacities based on DPPH radical scavenging assay. A total of 21 phenolic herb-markers were selected according to the similarity and principal component analysis of the chromatographic fingerprinting profiles. Their structures were further elucidated by UV, HPLC-DAD-ESI-QTOF-MS/MS and NMR analyses. The identified compounds included 2 phenylpropanoids, 11 C -glycosylflavones and 6 O -glycosylflavones, which could be employed as the indicators for quantitative evaluation of the quality and authenticity of the flowers. Based on the pre-column DPPH/ABTS + -HPLC analysis, the major compounds contributed to the antioxidative activity were identified as 1- O -caffeoyl- β -D-glucoside, rutin and isoquercitrin, all of which, were also the most abundant constituents in the methanolic extract. The results suggest the potential of D. catenatum flowers as a new antioxidant resources for medicinal and food products. Graphical abstract: Unlabelled Image Highlights: Flowers of D. catenatum are new food ingredient and exhibit potential antioxidant activities. 21 phenolic markers were identified by ESI-QTOF-MS/MS and NMR. 1- O -caffeoyl- β -D-glucoside, rutin and isoquercitrin were the dominant antioxidants in the flowers. The phenolics can be used as the markers for quality monitoring of flower products.